ANALISIS PENETAPAN PENGADILAN TERHADAP ANAK PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA (STUDI KASUS: PENETAPAN PENGADILAN NEGERI SURABAYA DAN 2 (DUA) PUTUSAN PENGADILAN NEGERI JAKARTA BARAT) - Lie Natania; Mety Rahmawati (Jurnal Hukum Adigama, 2018)
Children are the future of  mankind, our nation and country. Based on this strategic position, the state and the law must provide special protection for children. However, in finding themselves,in some occasions children can stumble and make mistakes, which unfortunately can be in the form of run-ins with the law. Act Number 11 of Year 2012 regarding the Criminal Justice System for Juvenile presented the concept of diversion, which is an approach to resolve juvenile cases in order to achieve restorative justice. Diversion is the of process diverting child cases out of the usual system of criminal justice. However, diversion cannot be used to resolve all and every child cases. In a case of drug abuse, as seen in the Verdict of Surabaya District Court Number 111/Pid.Sus-Anak/2014/PN.Sby, diversion is attempted to resolve the case. But in two similar cases, namely in the Verdict of West Jakarta District Court Number 47/Pid.Sus-Anak/2017/PN.Jkt.Brt and Number 53/Pid.Sus-Anak/2017/PN.Jkt.Brt, diversion was not attempted resolve the children in those cases and as stated on the verdict, those children were convicted. Why is there a difference in the resolution of the court against children who committed drug abuse between the Verdict of Surabaya District Court Number 111/Pid.Sus-Anak/2014/PN.Sby, the Verdict of West Jakarta District Court Number 47/Pid.Sus-Anak/2017/PN.Jkt.Brt and the Verdict of West Jakarta District Court Number 53/Pid.Sus-Anak/2017/PN.Jkt.Brt?